2017
DOI: 10.1051/e3sconf/20171903032
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the influence of coolant-lubricant modification on selected effects of pull broaching

Abstract: Abstract:The paper presents the results of testing the wear of the tool (pull broach) and a gear wheel splineway surface roughness after the friction node of pull broach/gear wheel (CuSn12Ni2) had been lubricated with metal machining oil and the same oil modified with chemically active exploitation additive. To designate the influence of modifying metal machining oil by the exploitation additive on the lubricating properties, anti-wear and antiseizure indicators have been appointed. Exploitation tests have pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…John et al [15] demonstrated that a certain concentration of surfactant could help accelerate the formation of a more stable emulsion and improve its performance. Adamczuk et al [16] observed a reduction in the roughness parameter Ra on a workpiece surface and an improvement in the durability of a pull broach upon modifying metal machining oil with an active additive during broaching. Sukirno and Ningsih [17] showed that the surface roughness, bearing capacity, and extreme pressure properties of palm oil with a sulfurized additive were significantly improved in broaching.…”
Section: Introductionmentioning
confidence: 99%
“…John et al [15] demonstrated that a certain concentration of surfactant could help accelerate the formation of a more stable emulsion and improve its performance. Adamczuk et al [16] observed a reduction in the roughness parameter Ra on a workpiece surface and an improvement in the durability of a pull broach upon modifying metal machining oil with an active additive during broaching. Sukirno and Ningsih [17] showed that the surface roughness, bearing capacity, and extreme pressure properties of palm oil with a sulfurized additive were significantly improved in broaching.…”
Section: Introductionmentioning
confidence: 99%